Negotiating The Identity Of Punk Children Amidst Social Diversity In The City Of Semarang - Muhammad Azyumardi Azra; Tholkhatur Khoir (UNIVERSITAS PAKUAN, 2025)
This research examines the identity negotiation process of punk children in the city of Semarang as part of subcultural dynamics in the context of a pluralistic urban society. Punk children are positioned as a marginalized group that faces stigma and social exclusion, but also shows adaptive capacity through various resistance strategies and community solidarity. Using a qualitative approach with phenomenological methods, data was collected through participant observation, in-depth interviews and documentation. The research results show that punk children negotiate their identity through symbolic performativity, situational adaptation, use of digital space, as well as social and artistic activities that build dialogue with the wider community. Community and internal solidarity play an important role in forming and maintaining collective identity amidst external pressures. This study confirms that subcultural identities are dynamic, and punk subculture is an alternative form of expression that contributes to the city's social diversity. These findings highlight the importance of a humanist approach in understanding the existence of subcultures as a legitimate part of urban society.